PERBANDINGAN PENGARUH STRATEGI PEMBELAJARAN INDEX CARD MATCH DENGAN GIVING QUESTIONS AND GETTING ANSWERS TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 3 TANJUNG RAJA - Laila Eprilia; Siti Fatimah; Dewi Koryati (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2018)
This research aims to know about comparison effect of learning strategy of Index Card Match with Giving Questions and Getting Answers to students' learning outcomes on economic subjects in SMA Negeri 3 Tanjung Raja. The problem formulation is "whether there is comparison effect of learning strategy of Index Card Match with Giving Questions and Getting Answers to students' learning outcomes on economic subjects in SMA Negeri 3 Tanjung Raja". This is an experimental research, using completely randomized design, with pretest posttest. Population in this research are all class X in SMA Negeri 3 Tanjung Raja. The sample of this research used cluster random sampling, so chosen X2 class as experiment class 1 and X3 as experiment class 2 which each amounted to 36 students. Data collection techniques used tests and observations.Data analysis techniques used to use regression analysis and partial correlation. Hypothesis used parametric statistic that is one way anova and obtained value of count bigger than F table hence hypothesis of Ho refused and Ha accepted. Then it could be concluded that there was a difference influence Index Card Match strategy with Giving Questions and Getting Answers to students'learning outcomes.